Clonal diversity of methicillin-resistant Staphylococcus aureus (MRSA) from bloodstream infections in northern Japan: Identification of spermidine N-acetyltransferase gene (speG) in staphylococcal cassette chromosomes (SCCs) associated with type II and IV SCCmec. (March 2021) - Aung, Meiji Soe; Urushibara, Noriko; Kawaguchiya, Mitsuyo; Hirose, Mina; Ito, Masahiko; Habadera, Satoshi; Kobayashi, Nobumichi
Highlights: In northern Japan, the most common SCC mec type in bloodstream infections was IIa. USA300 clone (PVL-positive MRSA-IVa, ST8/spa-t008) accounted for 5.1% of the MRSA. This suggests its increasing trend in Japan. Two MRSA isolates harboured speG and showed spermine resistance. speG in the two MRSA was located in additional SCCs close to SCC mec -II and IV. Abstract: Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the leading causes of bloodstream infections (BSIs). We aimed to study molecular epidemiological characteristics of MRSA isolates from BSIs in northern Japan to elucidate the recent trend of their clonal diversity. Methods: MRSA isolates ( n = 277) were collected from blood samples of patients who attended healthcare facilities in Hokkaido, the northern main island of Japan, for a two-year period from August 2017. Genotypes, virulence factors/drug-resistance determinants, and structure of SCC mec complex were analysed by PCR and sequencing analysis. Results: SCC mec -IIa ( n = 171, 61.7%) with coagulase genotype ( coa -) II, ST5/ST764/ST2389 was the most common genetic trait, followed by SCC mec -IVa ( n = 78, 28.2%), and IVl ( n = 10, 3.6%). Among the MRSA-IVa, 14 isolates (5.1% of all the isolates) had genetic features identical to USA300 clone (ST8/ coa -IIIa/ spa -t008 having ΦSa2USA and ACME-I), while PVL/ACME-negative MRSA-IVa isolates ( n = 64) were classified into coa -IIa/IIIa/VIIa/VIIb, with coa -VIIa/ spa -t1784/ST1 being dominant. Other minor clones included ST8-SCC mec -I, and ST30/ST45/ST81/ST121/ST1232-SCC mec -V, among which the ST1232 isolate harboured PVL genes. Spermidine N -acetyltransferase gene ( speG ), which is typically present in ACME-I of USA300 clone, was also identified in two isolates, ACME-II'-positive ST764-MRSA-IIa and ACME-negative ST1-MRSA-IVa, showing resistance to spermine. speG of these isolates was located in additional SCCs adjacent to SCC mec . Conclusions: Our present study revealed clonal diversity of MRSA from BSIs in Japan, with increased prevalence of ST8-USA300. Distinct types of speG -carrying SCCs associated with SCC mec -II or IV were identified.